An optimal fourth-order second derivative free iterative method for nonlinear scientific equations - Ghulam Akbar Nadeem; Waqas Aslam; Faisal Ali (Kuwait Journal of Science)
In the present paper, we develop an efficient second derivative free two-step optimal fourth-order iterative method for nonlinear equations. We explore the convergence criteria of the proposed method and also exhibit its validity and efficiency by considering some test problems. We present both numerical as well as graphical comparisons. Further, the dynamical behavior of the proposed method is explored.